The role of bank credits in investment financing of the small and medium-sized enterprise sector in Poland - Duda, Joanna (Managerial Economics, 2013)
Innovativeness of enterprises is largely dependent on their ability to obtain investment capital. Problems encountered by the SME sector when trying to obtain bank credits are commonly mentioned, therefore this paper attempts to evaluate the role of bank credits in financing investment activities of Polish SMEs on the basis of available literature and empirical research. To this end, sources of financing were analysed, focusing in particular on crediting offered to small and medium-sized enterprises, costs and terms of obtaining credits are presented in reference to the structure of actual investments.